A preclinical model to investigate the role of surgically‐induced inflammation in tumor responses to intraoperative photodynamic therapy. Issue 5 (25th May 2018) - Davis, Richard W.; Papasavvas, Emmanouil; Klampatsa, Astero; Putt, Mary; Montaner, Luis J.; Culligan, Melissa J.; McNulty, Sally; Friedberg, Joseph S.; Simone, Charles B.; Singhal, Sunil; Albelda, Steven M.; Cengel, Keith A.; et al.
Abstract : Objective: Inflammation is a well‐known consequence of surgery. Although surgical debulking of tumor is beneficial to patients, the onset of inflammation in injured tissue may impede the success of adjuvant therapies. One marker for postoperative inflammation is IL‐6, which is released as a consequence of surgical injuries. IL‐6 is predictive of response to many cancer therapies, and it is linked to various molecular and cellular resistance mechanisms. The purpose of this study was to establish a murine model by which therapeutic responses to photodynamic therapy (PDT) can be studied in the context of surgical inflammation. Materials and Methods: Murine models with AB12 mesothelioma tumors were treated with either surgical resection or sham surgery with tumor incision but no resection. The timing and extent of IL‐6 release in the tumor and/or serum was measured using enzyme‐linked immunosorbent assay (ELISA) and compared to that measured in the serum of 27 consecutive, prospectively enrolled patients with malignant pleural mesothelioma (MPM) who underwent macroscopic complete resection (MCR). Results: MPM patients showed a significant increase in IL‐6 at the time MCR was completed. Similarly, IL‐6 increased in the tumor and serum of mice treated with surgical resections. However, investigations that combine resection with another therapy make it necessary to grow tumors for resection to a larger volume than those that receive secondary therapy alone. As the larger size may alter tumor biology independent of the effects of surgical injury, we assessed the tumor incision model. In this model, tumor levels of IL‐6 significantly increased after tumor incision. Conclusion: The tumor incision model induces IL‐6 release as is seen in the surgical setting, yet it avoids the limitations of surgical resection models. Potential mechanisms by which surgical induction of inflammation and IL‐6 could alter the nature and efficacy of tumor response to PDT are reviewed. These include a wide spectrum of molecular and cellular mechanisms through which surgically‐induced IL‐6 could change the effectiveness of therapies that are combined with surgery. The tumor incision model can be employed for novel investigations of the effects of surgically‐induced, acute inflammation on therapeutic response to PDT (or potentially other therapies). Lasers Surg. Med. 50:440–450, 2018. © 2018 Wiley Periodicals, Inc.